2017
DOI: 10.4102/sajbm.v48i3.36
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IT adoption in SMEs supply chains: A case of Gauteng and Free State provinces of South Africa

Abstract: This study probed the influence of information technology adoption by small and medium enterprises (SMEs) in Gauteng and Free State Provinces of South Africa. The supply chain integration and collaboration of the SMEs was also explored to ascertain the IT influence. A quantitative methodology was used as it was the best way to measure the extent of the information technology (IT) influence. The participants were sent questionnaires via the e-mail and provided feedback to the researcher via the same medium. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…One previous study on telecommunications employees whose work combined advanced technologies with high levels of innovation found that the extent of trust within the technology-reliant workforce determined the amount of team-level cooperation [38]. Training employees to have strong technological skills promoted knowledge enhancement in the performance of tasks related to business in an organization [39]. Yu et al [40] found that technology enhanced knowledge management in the work environment, which entailed knowledge creation and knowledge sharing and gave the organization a competitive advantage that allowed it to increase its technological innovation.…”
Section: The Moderating Role Of Collaborative Technologymentioning
confidence: 99%
“…One previous study on telecommunications employees whose work combined advanced technologies with high levels of innovation found that the extent of trust within the technology-reliant workforce determined the amount of team-level cooperation [38]. Training employees to have strong technological skills promoted knowledge enhancement in the performance of tasks related to business in an organization [39]. Yu et al [40] found that technology enhanced knowledge management in the work environment, which entailed knowledge creation and knowledge sharing and gave the organization a competitive advantage that allowed it to increase its technological innovation.…”
Section: The Moderating Role Of Collaborative Technologymentioning
confidence: 99%
“…In Gauteng province, the SMMEs created about 150,000 jobs in a single year, and this was as a direct result of government's support to SMMEs [49]. Therefore, it is imperative that township SMMEs receive necessary interventions and support to address many of the challenges faced by the country [11].…”
Section: The Role Of Township Smmes In the Economymentioning
confidence: 99%
“…However, various studies have been conducted around SMMEs in South Africa, precluding the township context [9][10][11][12][13]. Reference [14] agreed that literature on small businesses focuses on other SMME contexts as a whole, while far less research has focused on the township SMME context.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted around SMMEs in SA, precluding the township context (Cant et al 2015;Ismail, Jeffrey & Belle 2011;Mathu & Tlare 2017;Pillay 2016;Turpin 2018). To better determine the factors affecting ICT adoption by township SMMEs and construct an ICT adoption framework, it is necessary to broadly understand the township environment, including their historical background.…”
Section: Introductionmentioning
confidence: 99%